Impetus of US hospital leaders to invest in patient-reported outcome measures (PROMs): a qualitative study. Issue 7 (6th July 2022) - Mou, Danny; Mjaset, Christer; Sokas, Claire M; Virji, Azan; Bokhour, Barbara; Heng, Marilyn; Sisodia, Rachel C; Pusic, Andrea L; Rosenthal, Meredith B
Abstract : Objectives: Though hospital leaders across the USA have invested significant resources in collection of patient-reported outcome measures (PROMs), there are very limited data on the impetus for hospital leadership to establish PROM programmes. In this qualitative study, we identify the drivers and motivators of PROM collection among hospital leaders in the USA. Design: Exploratory qualitative study. Setting: Thirty-seven hospital leaders representing seven different institutions with successful PROMs programs across twenty US states. Methods: Semistructured interviews conducted with hospital leaders. Transcripts were analysed using thematic analysis. Results: Leaders strongly believe that collecting PROMs is the 'right thing to do' and that the culture of the institution plays an important role in enabling PROMs. The study participants often believe that their institutions deliver superior care and that PROMs can be used to demonstrate the value of their services to payors and patients. Direct financial incentives are relatively weak motivators for collection of PROMs. Most hospital leaders have reservations about using PROMs in their current state as a meaningful performance metric. Conclusion: These findings suggest that hospital leaders feel a strong moral imperative to collect PROMs, which is also supported by the culture of their institution. Although PROMs are used in negotiations with payors, direct financial return on investment is not a strong driver for the collection of PROMs. Understanding why leaders of major healthcare institutions invest in PROMs is critical to understanding the role that PROMs play in the US healthcare system.